Advances in sarcopenia and urologic disorders - Zhao, Tonglei; Mao, Weipu; Hu, Mingjin; Yu, Qingyang; Peng, Xinyang; Ji, Jie; Qiu, Jianguo; Wu, Jianping (Frontiers in Nutrition, 2024)
Sarcopenia is a loss of muscle strength, muscle mass, and function that can increase a patient's risk of injury, illness, and can even severely impair quality of life and increase a patient's risk of death.A growing body of research suggests that sarcopenia and urinary tract disorders are closely related.In this review, we aimed to emphasize the definition of skeletal sarcopenia, summarize the methods used to diagnose skeletal sarcopenia, discuss the advances in the study of sarcopenia in benign diseases of the urinary system, discuss the advances in the study of sarcopenia in malignant diseases of the urinary system. Sarcopenia and urologic diseases interact with each other; urologic diseases cause sarcopenia, and sarcopenia aggravates the condition of the original disease, thus falling into a vicious circle. This review provides a comprehensive understanding of sarcopenia in urologic diseases, which is very important for the management and prognosis of urologic diseases.